Field notes contributed by B.J. Rose, spring 1987 - Rose, B.J.et al (1987)
List of birds and locations contributed by B.J. Rose with observer Douglas Rose. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1987. Epson - sheet feed